Data Transfer Management In Grid-Based Mass Storage Environment. - Sumari, Putra; Haron, Fazilah; Sodhy, Gian Chand; Yong, Chan Huah (2004)
The drastic increase in the data requirements of scientific applications and collaborative research has resulted of transferring a large amount of data among participating sites.